Protocol for the VAL-MAP 2.0 trial: a multicentre, single-arm, phase III trial to evaluate the effectiveness of virtual-assisted lung mapping by bronchoscopic dye injection and microcoil implementation in patients with small pulmonary nodules in Japan - Keiko Ueda; Yukari Uemura; Masaaki Sato (BMJ Open)
Introduction Tumour localisation is important for successful resection of lung nodules with optimal resection margins in sublobar resection. Virtual-assisted bronchoscopic localisation technique combined with dye marking and microcoil placement (VAL-MAP 2.0) is a minimally invasive, virtual-assisted, bronchoscopic technique that combines dye marking and microcoil implementation. As indwelling microcoils can provide information on the depth from the lung surface, they can be applied for deeply located small lung tumours that are barely identifiable by surface dye marking. This proposed study will examine the effectiveness of VAL-MAP 2.0 in patients with small pulmonary nodules.Methods and analysis This is a multicentre, prospective, single-arm, clinical trial. A total of 65 patients will be registered to undergo VAL-MAP 2.0 followed by thoracoscopic surgery. The primary outcome is successful resection, defined as resection of the lesion with optimal resection margins. The goal of the study is the achievement of a successful resection rate of 80%.Ethics and dissemination The study was approved by the Clinical Research Review Boards of the University of Tokyo (approval number 218 003SP) for all institutes, and the Technical Review Board for Advanced Medicine Category B of the Ministry of Health, Labour and Welfare. Results of the primary and secondary endpoints will be submitted for publication in a peer-reviewed journal.Trial registration number jRCTs031180099